Registration of Short Impulses of X-Ray Radiation Using the Detecting Block Based on GaAs Detectors; IEEE International Siberian Conference on Control and Communications (SIBCON-2007), Russia, Tomsk, April 20-21, 2007 - Nadreev I. I.; Nam I. F. Irina Feliksovna; Rozhnev M. A.; Ryabkov S. A.; Tolbanov O. P.; Tyazhev A. V.; Rybka D. V.; Tarasenko V. F. Victor Fedotovich (2007, 2007)
Title screen